2018
DOI: 10.1109/trpms.2018.2839066
|View full text |Cite
|
Sign up to set email alerts
|

Novel Detection Scheme for X-Ray Small-Angle Scattering

Abstract: X-ray imaging techniques, including x-ray radiography and computed tomography, have been in use for decades and proven effective and indispensable in diagnosis and therapy due to their fine resolution and fast acquisition speed. However, the innate disadvantage of x-ray is the poor soft tissue contrast. Small-angle scattering signals were shown to provide unique information about the abnormality of soft tissues that is complementary to the traditional attenuation image. Currently, there is no effective small-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Cone‐beam CT (CBCT) is widely used in diverse fields 1 such as medical diagnosis and therapy, 2–4 preclinical imaging and research, 5–8 and structural analysis in material science 9–12 . The traditional circular and helical trajectories are standard geometries for CBCT imaging 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cone‐beam CT (CBCT) is widely used in diverse fields 1 such as medical diagnosis and therapy, 2–4 preclinical imaging and research, 5–8 and structural analysis in material science 9–12 . The traditional circular and helical trajectories are standard geometries for CBCT imaging 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Cone-beam CT (CBCT) is widely used in diverse fields 1 such as medical diagnosis and therapy, [2][3][4] preclinical imaging and research, [5][6][7][8] and structural analysis in material science. [9][10][11][12] The traditional circular and helical trajectories are standard geometries for CBCT imaging. 13 With the development of CBCT imaging technology, it has been found that irregular trajectories have many benefits or are necessary in some special cases.…”
Section: Introductionmentioning
confidence: 99%